Computational prediction of mi-rnas responsible for gene silencing in Helianthus Tuberosus by using cross phylogeny approach with Arabidopsis Thaliana - SUMIT GOVIL,; SHAILESH KUMAR, (International Journal of Pharma and Bio Sciences, 2017)
MicroRNAs (mi-RNAs) are conserved biomolecules that regulate gene expression at level of translation. miRNA play a critical role at various levels in an organism. This is to deduce mi-RNAs by computational methods where they are compared for homology in EST sequences of an organism. The Helianthus tuberosus called as father of plant migration, having number of silent genes during its acclimatization to new world. A genomic approach is used to classify and target various identifiers at the nucleic acid level which govern the entire acclimatization of this plant. Raw Express Sequence Tags (ESTs) of Helianthus tuberosus were downloaded from dbEST Database, after refinement, clustering, and assembly by TGICL program, contigs and singletons were generated which are stored in a local database. Mature miRNA and Stem Loop of Arabidopsis thaliana were compared to generated local database by BLAST, were 50 mi-RNAs precursors were identified which aligned to multiple contigs where mature mi-RNA also showed their presence. The region of contigs alignment with the mi-RNA precursors were given in Mirfinder program for calculation of free energy values. Total 10 contig region identified where presence of mi-RNA precursor was feasible taking into consideration both the BLAST e-values and Mirfinder energy score.